Autorytet religijny a wiara osobista i autonomia sumienia - STYCZEŃ, Tadeusz (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The author refers to the Biblical narrative of the drama of Abraham, whom God commands to sacrifice his son Isaac. Abraham’s dilemma was already philosophically explored by Kierkegaard in his Fear and Trembling. In the present considerations the author gives an analysis of the relation between authority (in particular religious authority) and the autonomy of conscience. Why does Abraham consent to obey God’s cruel command if God’s reasons are hidden from him? The only justifiable answer is that God’s reasons God had earlier revealed to Abraham were sufficiently strong so that now he does not need to ask any further questions. While the reasons of this particular command are still hidden from him, the authority of God has a sufficiently strong foundation in his eyes so that he can accept, by virtue of the authority of God, the command he cannot comprehend. Therefore, in this particular situation, all Abraham wants is to protect his son, Isaac, from losing faith in God’s love. The author poses the question of what determines the moral nature of duty. On the one hand, he points that a reference to the law−giving authority, external to the acting subject, is present not only in religious ethical systems (it can be found, for instance, in M. Schlick’s proposal of ethics). On the other hand, he observes that one can hardly conceive of a moral duty that does not involve the acting subject’s inner conviction about the rightness of his action. Thus, he says, one may conclude that the moral duty to perform a given action is determined by the combination of an external, transsubjective element (the command of the authority) and an internal, intrasubjective one (the subject’s recognition of the command and the decision to consider it as binding on the basis of this recognition). However, the command of the authority and the subject’s personal conviction are frequently in conflict. Thus the author continues to explore whether in such situations the subject should give priority to the authority or to his or her personal conviction. He also investigates the possibility that the realm of morality is inherently torn apart and incoherent already at its roots. Yet the author stresses that if Abraham’s inner struggle is perceived merely in terms of the conflict between his conscience and the authority of the command−giver, we will fail to grasp the essence of the dilemma he experiences. The «reasons of the heart,» to which Abraham gives prioroty over the «reasons of the reason» and in the name of which he has «suspended» the latter, do not stop being his own reasons. He does not perceive them directly, but he is convinced about their existence and about them being morally significant to him, because he believes that they must be morally significant to the One who has so far sufficiently proven himself to him as «expert» in issues of morality and whom he (Abraham) has for this reason absolutely trusted and absolutely believed. Therefore Abraham now considers as morally binding the reasons unknown to him, provided they are sufficient for God to make this strange command. According to a «secular» interpretation, the drama of Abraham can be perceived as a dilemma between the view in favor of total autonomy of conscience in issues of morality and the one that the source of moral duty lies in an authority which is external to the acting subject. Yet we must not fail to see that also the first position involves a reference to authority, even if it is the authority of conscience itself (as, for instance, in Kantian ethics). In his discussion of Kant’s position the author points that a moral judgment, which is simultaneously a cognitive act, appears as a result of the coincidence of an act of the subject and the duty generating object, which is external to the acting subject. A moral controversy presupposes that its sides are rational subjects capable of formulating arguments which support their respective positions and that they are open to the criterion of truth which is external to both of them. Without such a criterion of truth a moral controversy might turn into an irresolvable tragedy. Summarized by Cezary Ritter Translated by Dorota Chabrajska